2021
DOI: 10.3390/antibiotics10091122
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic Prescribing Patterns in Ghana, Uganda, Zambia and Tanzania Hospitals: Results from the Global Point Prevalence Survey (G-PPS) on Antimicrobial Use and Stewardship Interventions Implemented

Abstract: Antimicrobial resistance (AMR) remains an important global public health issue with antimicrobial misuse and overuse being one of the main drivers. The Global Point Prevalence Survey (G-PPS) of Antimicrobial Consumption and Resistance assesses the prevalence and the quality of antimicrobial prescriptions across hospitals globally. G-PPS was carried out at 17 hospitals across Ghana, Uganda, Zambia and Tanzania. The overall prevalence of antimicrobial use was 50% (30–57%), with most antibiotics prescribed belong… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
58
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
2

Relationship

2
7

Authors

Journals

citations
Cited by 58 publications
(67 citation statements)
references
References 34 publications
5
58
4
Order By: Relevance
“…The prevalence of antibiotic use found in this study is high compared to what was found in high-income countries, but similar to findings in other low- and middle-income countries [ 33 ]. In contrast, a lower prevalence of antibiotic use was reported in other studies from Kenya (46.7%) [ 34 ]; Tanzania (44%) [ 35 ]; countries of Ghana, Uganda, Zambia, and Tanzania in the Global PPS (30–57%, with overall prevalence of 50%) [ 36 ]; Brazil (52.2%) [ 37 ]; Northern Ireland (46.2%) [ 38 ]; and Belgium (27.1%) [ 39 ]. Cross-national differences may be accounted for by factors such as varying disease burden, antibiotic use guidelines, and policies across countries, including ease of access to antibiotics, differences in patients’ characteristics, and types of hospitals.…”
Section: Discussionmentioning
confidence: 78%
“…The prevalence of antibiotic use found in this study is high compared to what was found in high-income countries, but similar to findings in other low- and middle-income countries [ 33 ]. In contrast, a lower prevalence of antibiotic use was reported in other studies from Kenya (46.7%) [ 34 ]; Tanzania (44%) [ 35 ]; countries of Ghana, Uganda, Zambia, and Tanzania in the Global PPS (30–57%, with overall prevalence of 50%) [ 36 ]; Brazil (52.2%) [ 37 ]; Northern Ireland (46.2%) [ 38 ]; and Belgium (27.1%) [ 39 ]. Cross-national differences may be accounted for by factors such as varying disease burden, antibiotic use guidelines, and policies across countries, including ease of access to antibiotics, differences in patients’ characteristics, and types of hospitals.…”
Section: Discussionmentioning
confidence: 78%
“…A total of 76,176 adult patients with RT-PCR confirmed COVID-19 were included from 22 studies, with studies by Russell et al [44] (UK, 48,902 patients) and Puzniak et al [34] (US, 17,003 patients) comprising 86.5% of the overall study population. The mean age of patients, was 61 years (IQR 59 67, range 36-74) and mean proportion of male subjects was 54% (IQR [50][51][52][53][54][55][56][57][58][59][60][61][62][63].…”
Section: Patients Characteristicsmentioning
confidence: 99%
“…The increase in antibiotic use observed during this pandemic might have impacted and setback antimicrobial stewardship (AMS) efforts globally, especially in regions where AMS programmes are just starting as seen in Africa with previous knowledge and resource issues [56][57][58]. This is starting to change in Africa with a growing number of AMS activities to address identified concerns [59][60][61]. However, remarkably, in certain regions globally, specifically in Europe, there was a decline in antibiotic use overall in 2020, despite high antibiotic use in COVID-19 positive patients.…”
Section: Plos Onementioning
confidence: 99%
“…The increase in antibiotic use observed during this pandemic might have impacted and setback antimicrobial stewardship (AMS) efforts globally, especially in regions where AMS programmes are just starting as seen in Africa with previous knowledge and resource issues [61][62][63] . This is starting to change in Africa with a growing number of AMS activities to address identified concerns [64][65][66] . However, remarkably, in certain regions globally, specifically in Europe, there was a decline in antibiotic use overall in 2020, despite high antibiotic use in COVID-19 positive patients.…”
Section: -Discussionmentioning
confidence: 99%